The Role of iRhom2 in Metabolic and Cardiovascular-Related Disorders - Geesala, Ramasatyaveni; Issuree, Priya D.; Maretzky, Thorsten (Frontiers in Cardiovascular Medicine, 2020)
Chronic obesity is associated with metabolic imbalance leading to diabetes, dyslipidemia, and cardiovascular diseases (CVDs), in which inflammation is caused by exposure to inflammatory stimuli, such as accumulating sphingolipid ceramides or intracellular stress. This inflammatory response is likely to be prolonged by the effects of dietary and blood cholesterol, thereby leading to chronic low-grade inflammation and endothelial dysfunction. Elevated levels of proinflammatory cytokines such as tumor necrosis factor (TNF) are predictive of CVDs and have been widely studied for potential therapeutic strategies. The release of TNF is controlled by a disintegrin and metalloprotease (ADAM) 17 and both are positively associated with CVDs. ADAM17 also cleaves most of the ligands of the epidermal growth factor receptor (EGFR) which have been implicated in blood pressure regulation, endothelial dysfunction, atherogenesis, and cardiac remodeling. The inactive rhomboid protein 2 (iRhom2) regulates the cleavage of ADAM17-mediated TNF in myeloid cells. In addition, iRhom2 also regulates the ADAM17-mediated cleavage of EGFR ligands such as amphiregulin and heparin-binding EGF-like growth factor. Targeting iRhom2 has been considered a promising therapeutic strategy in chronic inflammatory diseases such as rheumatoid arthritis and lupus nephritis. However, what role this intriguing interacting partner of ADAM17 plays in the vasculature and how it functions in the pathologies of obesity and associated CVDs, are exciting questions that are only beginning to be elucidated. In this review, we consider the role of iRhom2 in cardiovascular-related pathologies such as atherogenesis and obesity by providing an evaluation of known iRhom2-dependent cellular and inflammatory pathways.